Inhibition of NEDD8 and FAT10 ligase activities through the degrading enzyme NEDD8 ultimate buster 1: A potential anticancer approach (review) - Tan K.-L.; Pezzella F. (Spandidos Publications, 2024)
The capabilities of tumour cells to survive through deregulated cell cycles and evade apoptosis are hallmarks of cancer. The ubiquitin-like proteins (UBL) proteasome system is important in regulating cell cycles via signaling proteins. Deregulation of the proteasomal system can lead to uncontrolled cell proliferation. The Skp, Cullin, F-box containing complex (SCF complex) is the predominant E3 ubiquitin ligase, and has diverse substrates. The ubiquitin ligase activity of the SCF complexes requires the conjugation of neural precursor cell expressed, developmentally down-regulated 8 (NEDD8) to cullin proteins. A tumour suppressor and degrading enzyme named NEDD8 ultimate buster 1 (NUB1) is able to recruit HLA-F-adjacent transcript 10 (FAT10)- and NEDD8-conjugated proteins for proteasomal degradation. Ubiquitination is associated with neddylation and FAT10ylation. Although validating the targets of UBLs, including ubiquitin, NEDD8 and FAT10, is challenging, understanding the biological significance of such substrates is an exciting research prospect. This present review discusses the interplay of these UBLs, as well as highlighting their inhibition through NUB1. Knowledge of the mechanisms by which NUB1 is able to downregulate the ubiquitin cascade via NEDD8 conjugation and the FAT10 pathway is essential. This will provide insights into potential cancer therapy that could be used to selectively suppress cancer growth. 2016, Spandidos Publications. All rights reserved.